ANALISIS PERBANDINGAN METODE EXPONENTIAL APPROACH DAN METODE IMPROVED ZERO POINT UNTUK MEMINIMUMKAN BIAYA PENDISTRIBUSIAN - JIANTARI, NI KADEK; GANDHIADI, G.K.; WIDIASTUTI, RATNA SARI (E-Jurnal Matematika; Vol 11 No 3 (2022), 2022)
The purpose of this study is to do a comparative of the minimum cost of distributing mountea drinks using the exponential approach and the improved zero point method. The exponential approach method is a direct method where the allocation in this method depends on the number of zeros that appear in the transportation table. In the case of an unbalanced transportation problem, a dummy line (column) will appear where the cost on the line (column) is zero, which will greatly affect the optimum results of the given exponential approach method. The improved zero point method is an improved method from the zero point method, which is very useful for solving all types of transportation problems. This method provides an optimal solution without the help of other modified methods. Based on the results of the research, it was shown that the distribution cost of mountea drinks from the wholesale center in the Lunyuk sub-district using an exponential approach and an improved zero point obtained a cost of 10,392,276 Rupiah before the optimization, while the while the comparative distribution cost of the mountea drinks from the wholesale center in the Lunyuk sub-district after the optimization using an exponential approach and an improved zero point obtained a cost same of 8.552.560 Rupiah.